Inovasi Pelayanan Publik “SI LAKU O2T” di Kolaka Utara Sulawesi Tenggara - Mayunita, Sry (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2023)
Good public services can be recognized and assessed by implementation that meets service standards. In reality, the services currently provided often do not meet community expectations. What is even more worrying is that people do not fully understand what services they will receive according to procedures. This research was conducted using qualitative research methods at the Population and Civil Registration Service of North Kolaka Regency. The informant identification technique is snowball sampling and uses data analysis techniques (data reduction, data presentation, drawing conclusions). The findings show that the implementation of the Si Laku O2T Public Service Innovation Program in North Kolaka has simplified service requirements and procedures and reduced bureaucracy through establishing service standards. Overall, service implementation runs well from various aspects such as service operations, service completion time, service costs, service equipment and infrastructure, as well as service provider capabilities. However, more attention must be paid to the service completion time because the actual time required does not match the time specified in the service criteria.